Bipolar or monopolar electrosurgery in blepharoplasty: A comparison of surgical outcomes and patient satisfaction. (21st July 2020) - Kim, Jeenam; Kwon, Yongseok; Jun, Dong‐keun; Lee, Myungchul; Shin, Donghyeok; Kim, Soonheum; Jo, Dongin; Kim, Cheolkeun; Kim, Heonjoon; Choi, Hyungon
Abstract: Background: An electrosurgery unit (ESU) is the mainstay of bleeding control in blepharoplasty. There are two different types of ESUs: monopolar (m‐ESU) and bipolar (b‐ESU). Aims: We used m‐ and b‐ESUs in upper, lower, and combined blepharoplasty and compared their outcomes. Patients/Methods: In this retrospective file review of 292 blepharoplasty patients, we excluded 14 who were lost to follow‐up or had missing data; among the 278 enrolled patients, we recorded operative time, a surgeon panel's score for edema and ecchymosis on the third postoperative day, patients' scores of their satisfaction and inconvenience, and postoperative complications. Results: One hundred thirty‐nine patients were included in the m‐ESU and b‐ESU group. Overall, 105 patients underwent upper blepharoplasty, 77 underwent lower blepharoplasty, and 96 underwent combined blepharoplasty. The total mean operative time in the m‐ESU and b‐ESU was 67.94 and 62.82 minutes, respectively. This difference was not significant ( P > .05). The panel's edema and patient satisfaction and inconvenience scores were significantly better in the b‐ESU group ( P < .05). There were no significant differences in the panel's ecchymosis score and frequency as well as nature of complications between the m‐ESU and b‐ESU group ( P > .05). Conclusions: In this cohort of blepharoplasty patients, minimally invasive b‐ESUs were efficient in obtaining reliable surgical results with higher satisfaction and lower inconvenience rates of patients than m‐ESUs. We would like to recommend the use of b‐ESUs in blepharoplasty, especially for plastic surgeons inexperienced in periorbital esthetic surgery.